POEMS syndrome complicated by portal hypertension resembling decompensated cirrhosis: a case report and diagnostic insights - Zhou, Hua; Zhou, Yangdong; Wu, Lifang; Yan, Ling; Wei, Jie; Chen, Weixian; Huang, Xi; Zhang, Shaocheng (Frontiers in Medicine, 2025)
A 39-year-old woman presented with progressive fatigue and abdominal distension over 6 months, accompanied by limb numbness in the last 3 months. She was initially diagnosed with decompensated cirrhosis at another hospital, with ascites and esophagogastric varices. Symptoms partially improved with diuretic therapy. However, 3 months later, she developed peripheral neuropathy characterized by “numbness in hands, lower legs, and feet, with a cotton–wool sensation while walking.” Further investigations at our hospital revealed immunoglobulin A (IgA)-λ type M-protein by immunofixation electrophoresis (IFE), elevated vascular endothelial growth factor (VEGF) (145.96 pg/mL), multiple lymphadenopathies, and endocrine abnormalities (hypothyroidism and menstrual irregularities), leading to a diagnosis of Polyneuropathy, Organomegaly, Endocrinopathy, M-protein, Skin changes (POEMS) syndrome. Following chemotherapy with the carfilzomi, pomalidomide, and dexamethasone (KPD) regimen and autologous hematopoietic stem cell transplantation (ASCT), the patient showed significant improvement in neurological function and systemic symptoms. This case highlights that after excluding common causes of cirrhosis, such as viral hepatitis, autoimmune liver disease, Wilson's disease, and metabolic dysfunction-associated steatohepatitis (MASH), the patient received repeated symptomatic treatment for cirrhosis. Furthermore, the cirrhotic facies resembled the skin hyperpigmentation of POEMS syndrome, contributing to atypical presentations and diagnostic delay. POEMS syndrome should be suspected in patients with unexplained cirrhosis, ascites, and multisystem damage. Immunofixation electrophoresis for monoclonal protein is crucial for definitive early diagnosis, and VEGF testing also holds certain diagnostic significance.